Population growth and development of educational services for educational levels under higher education in Lattakia province – Syria - Sood , Ruba (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research highlights the development of education in Lattakia province and its keeping up with population growth to study the developments achieved by the educational process in the province and to analyze these developments and the factors they affected by in order to highlight the current situation and to determine results and limitations contributed to this development. The research aims to determine the current situation of education in Lattakia province after the availability of data required for development of education for all its levels. Research methodology depends on Deductive Approach, Synthetic Analytical Approach and Inductive Approach that depends on the development of geographical phenomenon studied during particular period. In the context of the development of the educational situation in Lattakia province, we found that internal competencies including preparation of educational and scientific staffs in the province and their tools was somewhat successful according to the existing data, while opportunities for success of external competencies was less from the former one through the recognizing of lack of interest in technical and vocational education which data refers to the remarkable declining of its role currently. The school dropout problem was also recognized after their registration and before finishing of the basic educational level, even if its rate was somewhat low, but it leads to undesirable effects on economical and social return of the level.